Le educación ambiental para mejorar el desarrollo humano sostenible, Chota - Perú, 2014 - Loayza Palomino, Víctor Rafael (2019)
ABSTRACT Was developed and applied an environmentaleducation action plan to improve sustainable human development in Chota - Peru 2014; the plan was prepared considering activities related to environmental awareness (preparation of essays and opinion articles); ecological culture (waste treatment, environmental education for journalists and social communicators, care of water, and planting trees); and the role of the institutions of training (family, school and social media) with the participation of professionals from different specialties: educators, engineers, journalists and others; also students the Institute of higher education teaching "Our Lady of Chota" and of the Universidad Nacional Autónoma de Chota. Environmental education improved sustainable human development in Chota, by efficiency and effectiveness embodied in the action plan; journalistic scripts for radio, television and the internet were put into practice in different social media; They completed the papers offered for journalists and social communicators and ronderos farmers knowledge of environmental standards, as well as the planting of trees, experience of much meaning; an environmental impact assessment was also made and field diaries were used. A significant conclusion is that environmental education improve sustainable human development in Chota to the extent that generates relevant responses in students, professionals and people in general, what improves the quality of life.